Video denoising with adaptive temporal averaging - Prasath, V. B. Surya (Array, 2019)
Recently the proliferation of digital videos has increased exponentially due to availability of consumer cameras . Despite the improvement in the sensor technologies, one of the fundamental problems is that of noise affecting the video scenes. Recently, adaptive, pixel-wise, temporal averaging methods can advocate in denoising videos. In this work, we adapt the edge maps of frames within temporal averaging to guide the denoising away from the edges. This allows the filtering to remove noise in intermediate flat regions while respecting boundaries of objects better. The experimental results indicate that we can obtain improved video denoising results in comparison to other filtering methods.